Comparative Efficacy of the Generalized Anxiety Disorder 7-Item Scale and the Edinburgh Postnatal Depression Scale as Screening Tools for Generalized Anxiety Disorder in Pregnancy and the Postpartum Period. (August 2014) - Simpson, William; Glazer, Melanie; Michalski, Natalie; Steiner, Meir; Frey, Benicio N
Objective: About 24.1% of pregnant women suffer from at least 1 anxiety disorder, 8.5% of whom suffer specifically from generalized anxiety disorder (GAD). GAD is often associated with major depressive disorder (MDD). During the perinatal period, the presence of physical and somatic symptoms often makes differentiation between depression and anxiety more challenging. To date, no screening tools have been developed to detect GAD in the perinatal population. We investigated the psychometric properties of the GAD 7-item Scale (GAD-7) as a screening tool for GAD in pregnant and postpartum women. Methods: Two hundred and forty perinatal women ( n = 155 pregnant and n = 85 postpartum) referred for psychiatric consultation were enrolled. On the day of initial assessment, all women completed the GAD-7 and the Edinburgh Postnatal Depression Scale (EPDS). Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition–based diagnoses were made by experienced psychiatrists. Scores from the GAD-7 and EPDS were compared with the clinical diagnoses to evaluate the psychometric properties of the GAD-7 and EPDS when used as a screening tool for GAD. Results: The GAD-7 yielded a sensitivity of 61.3% and specificity of 72.7% at an optimal cut-off score of 13. Compared with the EPDS and the EPDS-3A subscale, the GAD-7 displayed greater accuracy and specificity over a greater range of cut-off scores and more accurately identified GAD in patients with comorbid MDD. Conclusion: Our findings suggest that the GAD-7 represents a clinically useful scale for the detection of GAD in perinatal women.